PENERAPAN ETIKA BISNIS ISLAM (STUDI KASUS TOKO BAJU ZIFA DESA TARIKAN, KUMPEH ULU) - Muhamad Aldo Liwal Islam; Maulana Yusuf; Aztyara Ismadharliani (Jurnal Kajian dan Penalaran Ilmu Manajemen, 2024)
This thesis is entitled "Implementation of Islamic Business Ethics in the Zifa Clothing Shop in Tarik Village, Kumpeh Ulu sub-district". Islamic business ethics are the pros and cons of running a business in accordance with Islamic values. The problems in this research are (1) how is Islamic business ethics implemented in the clothing Zifa? (2) what are the inhibiting and supporting factors in implementing Islamic business? This research aims to find out how Islamic business ethics are implemented and what factors hinder and support Islamic business ethics in the Zifa Shop in Tarikan Village. The research method used is a qualitative method using primary data, then the data collection tools used are interviews, observation and documentation. Data analysis is descriptive qualitative by means of data reduction, data presentation and conclusions. This research analyzes the anoraga theory, namely the principles of Islamic business ethics, namely honesty, accuracy, loyalty and discipline. It's just that from the four principles of Islamic business ethics there are obstacles to implementing the principle of accuracy in delivering products to consumers of the Zifa Clothing Shop in Tarikan Village.